If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(ax + -1a) + 6(x + 6) = 0 Reorder the terms: a(-1a + ax) + 6(x + 6) = 0 (-1a * a + ax * a) + 6(x + 6) = 0 (-1a2 + a2x) + 6(x + 6) = 0 Reorder the terms: -1a2 + a2x + 6(6 + x) = 0 -1a2 + a2x + (6 * 6 + x * 6) = 0 -1a2 + a2x + (36 + 6x) = 0 Reorder the terms: 36 + -1a2 + a2x + 6x = 0 Solving 36 + -1a2 + a2x + 6x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -1a2 + a2x + -36 + 6x = 0 + -36 Reorder the terms: 36 + -36 + -1a2 + a2x + 6x = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -1a2 + a2x + 6x = 0 + -36 -1a2 + a2x + 6x = 0 + -36 Combine like terms: 0 + -36 = -36 -1a2 + a2x + 6x = -36 Add '-6x' to each side of the equation. -1a2 + a2x + 6x + -6x = -36 + -6x Combine like terms: 6x + -6x = 0 -1a2 + a2x + 0 = -36 + -6x -1a2 + a2x = -36 + -6x Reorder the terms: 36 + -1a2 + a2x + 6x = -36 + -6x + 36 + 6x Reorder the terms: 36 + -1a2 + a2x + 6x = -36 + 36 + -6x + 6x Combine like terms: -36 + 36 = 0 36 + -1a2 + a2x + 6x = 0 + -6x + 6x 36 + -1a2 + a2x + 6x = -6x + 6x Combine like terms: -6x + 6x = 0 36 + -1a2 + a2x + 6x = 0 The solution to this equation could not be determined.
| x^2-5y^2-4x+4y-6=-6y^2-6y+10x-64 | | 84/x=8 | | 5y^2=11y^2 | | -2a+b=c | | 7(2p+3)=12 | | 6x-80=4x-100 | | 9x-7w+4x+7y+2y+3w= | | 3.25/2.5 | | -(x-8)+4=2(-5)+x | | 4(2)-4b=12 | | w/4=-1/60 | | C=b-2a | | t=(c-h)/(b-25) | | 8x-60=2(5-3x) | | q-34+q-47=q+34 | | 12x-16y=-18 | | 3.5w=52.5 | | 5=3x+11 | | q-34+q-47=q+37 | | 6i-6= | | 6-1x=7x+6 | | b-47+b-46=b+22 | | x-46=46 | | 6z-16+3z=7z+15 | | 4w-5x-y+3w+17x-4y= | | 200=-5(-5+5x) | | p-17=22 | | 3q+21+9q=14q | | 2x^4+6x^3-8x^2=0 | | 5x-3y+11w-2y-4w+7x= | | s+24+5s=9s-37 | | -n-5n=-6 |